A Phasin with Many Faces: Structural Insights on PhaP from Azotobacter sp. FA8 - Mezzina, Mariela Paula (2014)
Phasins are a group of proteins associated to granules of polyhydroxyalkanoates (PHAs). Apart from their structural role as part of the PHA granule cover, different structural and regulatory functions have been found associated to many of them, and several biotechnological applications have been developed using phasin protein fusions. Despite their remarkable functional diversity, the structure of these proteins has not been analyzed except in very few studies. PhaP from Azotobacter sp. FA8 (PhaPAz) is a representative of the prevailing type in the multifunctional phasin protein family. Previous work performed in our laboratory using this protein have demonstrated that it has some very peculiar characteristics, such as its stress protecting effects in recombinant Escherichia coli, both in the presence and absence of PHA. The aim of the present work was to perform a structural characterization of this protein, to shed light on its properties. Its aminoacid composition revealed that it lacks clear hydrophobic domains, a characteristic that appears to be common to most phasins, despite their lipid granule binding capacity. The secondary structure of this protein, consisting of α-helices and disordered regions, has a remarkable capacity to change according to its environment. Several experimental data support that it is a tetramer, probably due to interactions between coiled-coil regions. These structural features have also been detected in other phasins, and may be related to their functional diversity.